A new potential function for the calculation of contact forces in the combined finite–discrete element method. (8th August 2016) - Yan, C.Z.; Zheng, H.
Summary: Although the potential contact force proposed by Munjiza overcomes the difficulties inherent in the traditional discrete element methods, the physical meaning of the potential is not clear and the contact force derived from the original potential function is strongly dependent on the mesh configuration. In this study, we redefine a potential function and propose a new contact force calculation method based on a unified standard. Moreover, the new potential function retains all the advantages of the original potential function but has less mesh dependency. Copyright © 2016 John Wiley & Sons, Ltd.